A new subspecies of apolinar’s wren (cistothorus apolinari, aves: troglodytidae), an endangered colombian endemic (2002)
We describe Cistothorus apolinari hernandezi, subsp. nov. from wet páramo of theSumapaz massif south of Bogotá, Colombia. This form differs from the nominate ofthe wetlands of the Cundinamarca-Boyacá Plateau in size, coloration, ecology, socialstructure and song and appears to be isolated from it by some 1000 m of elevationand different habitat preferences. A second population apparently occurs some 300km further northeast in the Sierra Nevada del Cocuy in Dept. Boyacá but no dataexist for intervening páramos. As a species, C. apolinari is critically endangeredbut the wetland and páramo populations face different threats and require differentconservation strategies; distinguishing the latter population formally helps callattention to this situation.